Motherhood and Employment : Navigating Career Continuity in the Czech Republic and the United States - Bukačová, Veronika Zoe (2024)
Motherhood is regarded as a pivotal point in many women’s careers as it presents new priorities and challenges in work-life balance. Women in the Czech Republic and the United States make up nearly half of the labor market. Therefore, it is essential to include the perspectives of mothers in workforce representation to better understand their experiences of continuing their careers after childbirth. This thesis presents a comparative analysis of the challenges women in the workforce in the Czech Republic and the United States experience related to motherhood to bring awareness and understanding to the role of motherhood on career continuance. The theoretical part gives background to the female labor market participation, the role women play in the workforce, maternity and parental leave policies, flexible forms of work, and childcare support. The practical part presents qualitative research findings based on a thematic analysis of eight semi-structured in-depth interviews with Czech and American working mothers with children ages 6 years old and under. Research results show that Czech working mothers have access to extensive paid maternity and parental leave as well as subsidized early formal childcare. Their experience significantly differs from those of American working mothers, who only have access to short unpaid family leave. Czech and American women's decisions to rejoin the workforce after childbirth are driven mainly by financial needs, willingness to pursue career fulfillment beyond motherhood, and partner support. As a result of the research, the author offers suggestions on how to improve the work-life balance of working women with children in both countries.